Factors that affect export performance of MISC agencies Port Klang / Muhammad Faiz Zolkifli - Zolkifli, Muhammad Faiz (Faculty of Business and Management, 2012)
Exporting became a major component a major component of international trade based on the theory and history international trade itself. A large number of SMEs and MNCs which play role as a seller tend to ship the goods and serviced produced in home country out of the port of the country by using sea freight. MISC Berhad is Malaysian’s leading international maritime corporation and is currently third largest conglomerate in the world by market capitalisation. The purpose of this research is to identify factors that affect export performance of MISC Agencies which is a subsidiary of MISC Berhad. The researcher also aim to find out any other factors that can give impact to export performance as well as come out with several recommendations for a better study in the future research. As for this qualitative type research, the researcher used triangulation method as all the primary data from interviews are gathered and supported by the secondary data which is the internal and external sources. Based on findings part, factors such as firm size, export experience and price found out to give impact to export performance as supported besides there are also another factors found out can give impact to export performance as supported by the literature reviews.